Transição semicondutor-metal em nanocristais de VO2 termoeletricamente ativada - Silva, Luciane Janice Venturini da (2015)
In this thesis, structural and electrical characteristics are investigated around the thermally triggered semiconductor to metal transition in VO2 thin films. The films, the metallics electrodes, as well as SiO2 buffer layers have been deposited by reactive magnetron sputtering onto Si substrates. The crystallographic and morphological characteristics have been observed through measurements of X-Ray diffraction as a function of the temperature, and atomic force microscopy (AFM). The nanoscale electrical characterization have been performed using a measurement system via nano-tips. The results of X-ray diffraction at room temperature revealed that the samples are polycrystalline and are strongly textured in the < 011 > direction, which is almost perpendicular to the substrate plane. The X-Ray diffraction spectra have been extracted at different temperatures to follow the crystallographic transition experienced by VO2 near the transition temperature. For films deposited on SiO2 (without electrodes) and the Ta electrode at temperatures below the critical temperature for the transition, the material presented in the monoclinic phase M1. Within the range of temperatures that comprises the transition occurs progressive appearance of the peak corresponding to the (110) plane of R rutile phase. Within a range at relatively higher temperatures, there is a coexistence of phases R and M1 and M2 may be the M2 monoclinic. As would be expected, the peak of rutile structure grows to the point of being virtually the only present when the temperature reaches about 80°C. The transition from one crystallographic film VO2 with Pd electrode was accompanied by diffraction measured at room temperature. The peak (011) of phase M1 is much smaller compared to the samples deposited on Ta electrode. However, contrary to the Ta electrode film which is likely to have grown in the shape of very small nano-grain or even amorphous form, the Pd electrode film is polycrystalline and highly textured. The transport properties during the electrical phase transition were investigated using injection of electrical current perpendicular to the sample plane. Films grown on Ta electrodes showed abrupt semiconductor-metal phase transitions in different nano-crystallites VO2. The IV characteristics of the film on the Pd electrode had an S-NDR region, specifically attributed to the formation of a filamentary current flow between the Pd probe and the electrode. The details of this phenomenon could not be established definitively, but if in fact the electrical transition is present in nano-crystallites measured, it was suggested that the origin of this conducting channel may be related to reminiscent earlier phase transitions.